2018
DOI: 10.24875/ric.18002524
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Assessment Tools for the Identification of Malnutrition and Nutritional Risk Associated with Cancer Treatment

Abstract: Malnutrition and muscle wasting are common features of cancer cachexia that may interfere with the patient's response to cancer treatment, survival, and quality of life. An accurate nutritional screening at the time of diagnosis and throughout the patient's treatment fosters better control of the disease. Several screening tools have proven to be useful for this purpose. Nevertheless, nutritional evaluation is not a routine practice in this clinical setting and procedures must be standardized. Nutritional risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 15 publications
0
54
0
13
Order By: Relevance
“…Previous studies have shown that malnutrition, reflected by hypoalbuminemia, provides a favourable microenvironment for tumour recurrence. 25,28 A worse nutritional status leads to tumour progression through the suppression of tumour immunity. 34 Inflammatory blood cells, such as neutrophilia, play a fundamental role in generating high levels of reactive oxygen species (ROS), tumour necrosis factor-α (TNF-α) and macrophage migration inhibitory factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that malnutrition, reflected by hypoalbuminemia, provides a favourable microenvironment for tumour recurrence. 25,28 A worse nutritional status leads to tumour progression through the suppression of tumour immunity. 34 Inflammatory blood cells, such as neutrophilia, play a fundamental role in generating high levels of reactive oxygen species (ROS), tumour necrosis factor-α (TNF-α) and macrophage migration inhibitory factor.…”
Section: Discussionmentioning
confidence: 99%
“…23 Malnutrition, reflected by hypoalbuminemia, is associated with increased morbidity and mortality. 24 Several studies have shown that malnutrition also interferes with the patient’s response to cancer treatment, 25 and malnutrition is related to immunosuppression, which provides a favourable microenvironment for tumour recurrence. 26 , 27 The association between inflammation and tumours was first noticed by Virchow in 1863.…”
Section: Discussionmentioning
confidence: 99%
“…Serum total protein and albumin levels are used as indicators of nutritional status (Sasatani, Okauchi, Ohara, Kagohashi, & Satoh, 2020;Shen et al, 2020). Several studies have used body weight and BMI as indicators of general condition in patients receiving chemotherapy (Castillo-Martínez et al, 2018). Furthermore, pretreatment weight loss is a poor prognostic factor in lung cancer patients (Lau et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical symptoms along with body composition evaluation and molecular marker assessment could allow a detailed insight into a patient's condition and should be considered during nutritional screening prior to therapy. It could exclude selected patients from therapy, for whom the therapy complications could be worse than the benefits [111,112]. The assessment of molecular changes seems to be primarily useful because of its ability to objectively reflect the body's condition at the cellular level, including the nutritional status and mechanisms controlling this process.…”
Section: Itgam-323g>a [106]mentioning
confidence: 99%